New nutritional data on traditional foods for European food composition databases - Costa, H.S. (2011)
Background/Objectives: There are many different cultures within Europe, each with its own distinct dietary habits. Traditional foods are the key elements that differentiate the dietary patterns of each country. Unfortunately, in most countries, there is little information on the nutritional composition of such foods. Therefore, there is a need to study traditional foods to preserve these elements of European culture and, if possible, enrich and improve dietary habits across the continent. The Traditional Foods work package within the European Food Information Resource (EuroFIR) project aimed to provide new nutritional data on traditional foods for use in national food composition tables. Subjects/Methods: A EuroFIR consensus-based method with standardised procedures was applied for the systematic study of traditional foods and recipes in selected European countries. Traditional foods were selected on the basis of the EuroFIR definition of the term ‘traditional food’ and prioritised according to specific criteria. From the prioritised list, the five traditional foods per country to be investigated were selected to represent a full course meal. Protocols with guidelines for the recording of traditional recipes, the collection, preparation and distribution of laboratory samples, as well as quality requirements for laboratory selection, were developed to establish a common approach for use by all countries for the acquisition of reliable data. Results: The traditional character of the selected foods has been documented and traditional recipes have been recorded. Chemical analyses to determine the nutritional composition of 55 traditional foods were performed and the data were evaluated and fully documented according to EuroFIR standards. Information on food description, the recipe, component identification, sampling plan, sample handling, analytical method and performance was collected for each of the 55 investigated traditional foods. Conclusions: This common methodology for the systematic study of traditional foods will enable countries to further investigate their traditional foods and to continue to update their national food composition databases and EuroFIR’s food databank system.